Systemic risk, institutional design, and the regulation of financial markets - Anand, Anita, 1967- (Oxford : Oxford University Press, 2017)
A collection of essays from an impressive group of scholars, this volume disseminates the type of regulation that can be devised and implemented to respond to systemic risk as well as how systemic risk can be regulated in both a domestic and international market.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 9, 2016).
Keywords: Financial risk management; Financial institutions -- Law and legislation; Industry; Industry & industrial studies